Diagnostic challenges in von Willebrand disease. Report of two cases with emphasis on multimeric and molecular analysis. (4th July 2021) - Moreno-Castaño, AB; Ramos, A; Pino, M; Parra, R; Altisent, C; Vidal, F; Corrales, I; Borràs, N; Torramadé-Moix, S; Palomo, M; Escolar, G; Diaz-Ricart, M
Abstract: Identification of qualitative variants of von Willebrand disease (VWD) can be a diagnostic challenge because of discrepant results obtained in the multiple laboratory tests available for its appropriate classification. We report two cases of infrequent inherited variants of VWD with unclear preliminary results with the test panel available at the time of first consultation and that were finally diagnosed as a VWD type 2A/IID with a c.8318 G > C, p.Cys2773Ser mutation and a VWD type 2M with c.4225 T > G, p.Val1409Phe mutation, respectively. The description of these two cases highlights that despite the limited diagnostic panel for the evaluation of von Willebrand Factor (VWF) functionality, the multimeric analysis and genetic family studies were fundamental tools to achieve the final diagnosis.